2019
DOI: 10.1111/jace.16481
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport behavior of polymer‐derived amorphous silicoboron carbonitrides

Abstract: Electron transport behavior of polymer‐derived amorphous silicoboron carbonitride (a‐SiBCNs) ceramics was studied by measuring DC/AC conductivities and optical absorption as functions of the temperature. Structural information of materials was investigated by combining X‐ray diffraction (XRD), nuclear magnetic resonance (NMR), X‐ray photoelectron spectroscopy (XPS), Raman spectroscopy, and electron paramagnetic resonance (EPR) techniques. Conductive mechanisms and electronic structure of the materials (eg, hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…[4,61] σ of PDCs pyrolyzed at temperatures below 1300 °C is poor, usually being below 10 −5 S cm −1 at room temperature. [14,20,21,[62][63][64][65][66][67][68][69][70][71][72][73][74] Poor σ limits the functional applications of PDCs. For example, PDCs-based sensors are electrically insulated at room temperature and thus have high sensitivity only at high temperatures.…”
Section: Abnormal Electrical Behaviors In Pdc-sicnmentioning
confidence: 99%
“…[4,61] σ of PDCs pyrolyzed at temperatures below 1300 °C is poor, usually being below 10 −5 S cm −1 at room temperature. [14,20,21,[62][63][64][65][66][67][68][69][70][71][72][73][74] Poor σ limits the functional applications of PDCs. For example, PDCs-based sensors are electrically insulated at room temperature and thus have high sensitivity only at high temperatures.…”
Section: Abnormal Electrical Behaviors In Pdc-sicnmentioning
confidence: 99%
“…Polysiloxane‐derived SiC‐TiC composites are more likely to show even higher electrical conductivity since TiC is more conductive apart from free C and graphitic carbon. Previous studies have demonstrated certain electron transport mechanisms of PDCs, such as a variable‐range hopping mechanism 41 or a band‐tail hopping mechanism 42 for amorphous semiconducting behaviors, and an Arrhenius relationship 41 in the presence of crystalline phases. Thus, the electrical conductivity mechanisms of polymer derived SiC‐TiC should be elucidated in order to provide more guidance for tuning the electrical properties of PDC nanocomposites.…”
Section: Introductionmentioning
confidence: 99%